'Being an English major, being a humanities student': connecting academic subject identity in literary studies to other social domains. Issue 9 (1st September 2016) - Chan, Evelyn T.Y.
Abstract : This study examined students' construction of academic subject identity in a university humanities discipline, English literary studies. In so doing, the study aimed to provide an empirically grounded intervention in current debates on the value of the humanities in higher education. Eight students participated in interviews lasting 15–20 minutes each. Narrative methodology was aligned with the social constructionist paradigm to investigate identity construction and emergence. These showed students' creative agency as well as careful negotiation with existing social views. They revealed a variety of identity stability and conflict, determined by one key issue: whether or not students felt they could competently translate their subject identities into other social domains relevant to their lives. These findings improve current understanding of the value of humanities education by showing students' perspective instead of educational practitioners'. They also point to possible educational intervention strategies to increase students' competence in subject identity construction.